The Effect of Spiritual Intelligence Santri Tirakatan Islamic Boarding School Jagad ‘Alimussirry to Personal Financial Management - Damayanti, Novita Dwi (http://jagadalimussirry.com/, 2019)
Frequent discrepancies between income and expenditure by santri caused by a great desire to continue carrying out excessive consumption activities. Effectiveness and efficiency in financial management are closely related to the spiritual intelligence of each santri. SQ intelligence in managing personal finances will have an impact in driving good and right management goals. Allah in his word also gave an appeal to all his people to be able to manage well so that the realization of the benefit of life in the world and in the hereafter can be realized. The type of this research is the quantitative research methods. The research site was centered at the Islamic Boarding School Jagad ‘Alimussirry Wonokromo Surabaya. In this study shows that spiritual intelligence has no influence on the process of managing personal finance.